An Empirical Investigation of the Declining Sucrose Content in South African Sugar Cane - Doorasamy, Mishelle (Journal of Economics and Behavioral Studies, 2018)
This study is aimed at investigating the declining sucrose levels in South African sugar cane using principal component analysis. The agricultural production of sugar cane has been one of the major sources of income to the South African economy. Sucrose has been classified in the analysis of Brix percentage of sugarcane juice as one of the most important parameters of sugar composition, due to its usefulness, among the components in sugar cane which are needed for farmers to generate income within the economy. However, data indicates that the sucrose content decline which began in 2014 is still ongoing, representing great loss to the farmers. To investigate this trend, this study has regressed the sucrose percentage in cane as a dependent variable against the ratio in Tons of cane to 1 Ton of sugar, tons of cane crushed, tons of sugar made, and yields per hectare of harvested cane. The study used correlation matrices, summary statistics and principal component analysis as tools in carrying out its investigation. From the regression result, the proportional composition value of sucrose which stands at 0.6059 - the highest compared to others in the model - indicates that it is an essential component in the chain of sugar production. However, when the maximum value of sucrose (14.24000) is compared with its minimum (12.92000), a remarkable decline is observed. Since a remarkable difference is also observed when the mean value of 13.55353 is compared with the standard deviation value of 0.378318, the study can conclude that the percentage level of sucrose is low compared to other explanatory variables. This typically signifies a decline in the value of sucrose when compared with other variables under investigation.